The rural : knowing where we are by retracing our steps - Hallnäs, David (SLU/Dept. of Urban and Rural Development, 2017)
This thesis is a discourse analysis of rural studies literature, both rural soci-ology and rural geography, throughout depicted timely eras of Modernity, Late Modernity, Postmodernity and Relational Rural. It attempts to sort through vast literature, exemplifying a few works and postulating them as attempts under certain eras. This thesis aims to investigate how the concept rural has been understood and used over time. The thought behind this attempt is that a clearer under-standing of how the Rural has been conceptualised and reconceptualised will inform our present thought, allowing us a glimpse into where our scholarly efforts have been, and perhaps how we ended up with our present thoughts. It informs us that the rural has never been, nor will ever be a fixed concept. This overview allows us to trace concepts, as well as picking up on thoughts that have been left rather untouched, while also discerning some theoretical pitfalls along the way. Knowing where we are by retracing our steps.